Enhancing ambience product derived from clam state of mind - อินทุยศ ปวณัศ; กานต์สมเกียรติ ลุ้ย (Journal of Fine and Applied Arts Khon Kaen University, 2018)
The purpose of this research is to design an enhancing ambience product derived from calm state of mind that assist in meditation or Vipassana meditation and can be self-practice in residential. The objective of this research was 1) to study an idea about calm state of mind for guidance in designing product for all practical purpose relative with enhancing ambience product derived from calm state of mind. 2) to design and develop an enhancing ambience product derived from calm state of mind 3) to study satisfactions of sample focus group with the product. The result of this research showed that there are 2 types of calming 1) calm state in atmospheric and environment including private state of solitude warm tone color (White, Grey, Yellow) dim light that gives brightness in a specific point 2) a calm state of mind by using pattern (Mindful awareness) such as Anapanasati (Mindfulness of breathing) Sota-sati (Mindfulness of hearing) moving with awareness(Mindfulness of body movement) and solution for compression of body weight problem that cause feeling ache stiff or pain. Therefore the researcher bring all factor to designing which in product sets include lamp that create atmosphere, chair for meditation and natural sound imitation that help facilitate the mindfulness meditation practice and be able to self practice in privacy area also this research and develop the product sets concern in mindfulness meditation practice for more variety way and the better results. which result of satisfaction form sampling group who trials 30 person the analysis result reveal high in general 4.02 (S.D. = 0.74) and result from expert in product design and mindfulness meditation for 5 person the analysis result wast reveal high in general. 4.20 (S.D. = 0.50)